Item Fit Analysis for Evaluating Academic Writing Performance With Rasch Measurement - Rentiana, Leny Hikmah; Dhini, Ulfa Rahma; Yuliawati, Lilik; Wulandari, Eka Tri (CV. Creative Tugu Pena, 2024)
This study aims to evaluate item fit through the application of the Rasch model. The research involved 40 English as a foreign language student who took part in an essay writing class as part of a TOEFL iBT course, with writing samples gathered in partnership with the language center offering the TOEFL iBT classes. The research methodology utilizes the Rasch model with Winsteps software for quantitative analysis, employing three key statistical outputs: a